ANALISIS FILLING TIME DAN INJECTION PRESSURE UNTUK PRODUK CASE LINK FLOW WATER METER BERDASARKAN POSISI GATE MENGGUNAKAN METODE CAD - Rasidiq Karunia Sandy; Agus Nuramal; Ahmad Nizam (UNIB Press, 2026)
This research discusses the analysis of filling time and injection pressure on ABS (Acrylonitrile Butadiene Styrene) case link flow water meter products with variations in gate position using Computer-Aided Design (CAD) methods. The selection of the appropriate gate position significantly affects the efficiency of the injection process and the quality of the mold results. In this study, several gate position configurations are analyzed to determine their impact on filling time and injection pressure during the molding process. Simulations were conducted using CAD software integrated with a plastic injection analysis module. The analysis results indicate that a strategic gate position can minimize filling time and reduce Injection pressure up to 18% and reducing filling time by up to 12%, compared to other gate positions, thus increasing production process efficiency and reducing the risk of product defects. This research provides recommendations for the optimal gate position that can be applied in the production process of case link flow water meters to achieve better quality and productivity.